Autosomal dominant stromal corneal dystrophy associated with a SPARCL1 missense variant - Braddock, Freddie L; Gardner, Jessica C; Bhattacharyya, Nihar; Sanchez-Pintado, Beatriz; Costa, Marcos; Zarouchlioti, Christina; Szabo, Anita; Lišková, Petra; Cheetham, Michael E; Young, Robert D; Thaung, Caroline; Davidson, Alice E; et al. (European journal of human genetics, 2024)
Corneal dystrophies are phenotypically and genetically heterogeneous, often resulting in visual impairment caused by corneal opacification. We investigated the genetic cause of an autosomal dominant corneal stromal dystrophy in a pedigree with eight affected individuals in three generations. Affected individuals had diffuse central stromal opacity, with reduced visual acuity in older family members. Histopathology of affected cornea tissue removed during surgery revealed mild stromal textural alterations with alcianophilic deposits. Whole genome sequence data were generated for four affected individuals. No rare variants (MAF < 0.001) were identified in established corneal dystrophy genes. However, a novel heterozygous missense variant in exon 4 of SPARCL1, NM_004684: c.334G > A; p.(Glu112Lys), which is predicted to be damaging, segregated with disease. SPARC-like protein 1 (SPARCL1) is a secreted matricellular protein involved in cell migration, cell adhesion, tissue repair, and remodelling. Interestingly, SPARCL1 has been shown to regulate decorin. Heterozygous variants in DCN, encoding decorin, cause autosomal dominant congenital stromal corneal dystrophy, suggesting a common pathogenic pathway. Therefore, we performed immunohistochemistry to compare SPARCL1 and decorin localisation in corneal tissue from an affected family member and an unaffected control. Strikingly, the level of decorin was significantly decreased in the corneal stroma of the affected tissue, and SPARCL1 appeared to be retained in the epithelium. In summary, we describe a novel autosomal dominant corneal stromal dystrophy associated with a missense variant in SPARCL1, extending the phenotypic and genetic heterogeneity of inherited corneal disease.
Keywords: Corneal Stroma; Corneal Dystrophies, Hereditary; Humans; extracelulární matrix - proteiny; dekorin; Mutation, Missense; lidé středního věku; Calcium-Binding Proteins; Female; Aged; dospělí; senioři; dědičné dystrofie rohovky; lidé; Extracellular Matrix Proteins; Adult; Pedigree; rodokmen; missense mutace; ženské pohlaví; Decorin; Male; Middle Aged; proteiny vázající vápník; Heterozygote; heterozygot; mužské pohlaví; stroma rohovky